2016
DOI: 10.1038/srep31643
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising enterocolitis and mortality in preterm infants after introduction of probiotics: a quasi-experimental study

Abstract: Evidence on the clinical effectiveness of probiotics in the prevention of necrotising enterocolitis (NEC) in preterm infants is conflicting and cohort studies lacked adjustment for time trend and feeding type. This study investigated the association between the introduction of routine probiotics (Lactobacillus acidophilus and Bifidobacterium bifidum; Infloran®) on the primary outcome ‘NEC or death’. Preterm infants (gestational age <32 weeks or birth weight <1500 gram) admitted before (Jan 2008–Sep 2012; n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 41 publications
3
36
2
Order By: Relevance
“…Samuels et al . () reported that introduction of probiotics was associated with reduced adjusted odds for ‘NEC or sepsis or death’ only in exclusively breastmilk‐fed infants [OR: 0.43, 95% CI: 0.21–0.93, P = 0.03]. Our non‐RCT supports the benefits of probiotics in breastmilk‐fed preterm infants (Patole et al ., ).…”
Section: Evidence Supporting Benefits Of Probiotics In Preterm Infantsasupporting
confidence: 79%
See 1 more Smart Citation
“…Samuels et al . () reported that introduction of probiotics was associated with reduced adjusted odds for ‘NEC or sepsis or death’ only in exclusively breastmilk‐fed infants [OR: 0.43, 95% CI: 0.21–0.93, P = 0.03]. Our non‐RCT supports the benefits of probiotics in breastmilk‐fed preterm infants (Patole et al ., ).…”
Section: Evidence Supporting Benefits Of Probiotics In Preterm Infantsasupporting
confidence: 79%
“…(). Probiotics in breastmilk vs. formula‐fed infants: Many believe that probiotics are not required if the infant is fed breast milk – the ideal food provided by nature that contains many bioactive elements including probiotics, human milk oligosaccharides, and lactoferrin. The results of two non‐RCTs are important in this context (Repa et al ., ; Samuels et al ., ). Repa et al .…”
Section: Evidence Supporting Benefits Of Probiotics In Preterm Infantsamentioning
confidence: 97%
“…It is also important to mention that in preterm infants, despite the evidence of a certain level of risk, the administration of probiotics decreases the risk of NEC and decreases its mortality 38,39 .…”
Section: Casei L Plantarum L Acidophilus L Delbruecki Subsp Bumentioning
confidence: 99%
“…57 Preventive strategies, such as probiotics, holding feeds during transfusions, truncating antibiotic use during the first week, and providing exclusive human milk feedings have not eradicated the disease, and in some cases their efficacy has been refuted by randomized control trials. 812 For example, in a recent UK study, Costeloe et al 13 reported no effect of probiotics in a very large cohort, and a meta-analysis by Samuel et al 14 found no additional value of probiotics for infants who received breast milk. We clearly need better-defined mechanistic interventions to prevent NEC.…”
mentioning
confidence: 99%